2016
DOI: 10.1038/bjc.2016.291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of candidate biomarkers of prostate cancer progression in serum: a depletion-free 3D LC/MS quantitative proteomics pilot study

Abstract: Background:Prostate cancer (PCa) is the most common male cancer in the United Kingdom and we aimed to identify clinically relevant biomarkers corresponding to stage progression of the disease.Methods:We used enhanced proteomic profiling of PCa progression using iTRAQ 3D LC mass spectrometry on high-quality serum samples to identify biomarkers of PCa.Results:We identified >1000 proteins. Following specific inclusion/exclusion criteria we targeted seven proteins of which two were validated by ELISA and six poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…The GO is a structured and controlled vocabulary of terms, and widely recognized as the premier tool for the organization and functional annotation of molecular characteristics [18,20,21]. By interpreting the GO of differentially expressed proteins and then analyzing them statistically, we have obtained 42 significant CSF proteins and 57 significant plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO is a structured and controlled vocabulary of terms, and widely recognized as the premier tool for the organization and functional annotation of molecular characteristics [18,20,21]. By interpreting the GO of differentially expressed proteins and then analyzing them statistically, we have obtained 42 significant CSF proteins and 57 significant plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic technologies have been largely used to search for differentially expressed proteins, in order to clarify the diagnosis and prognosis of diseases such as tumor and neurodegenerative disorders [14][15][16]. Isobaric tags for relative and absolute quantitation (iTRAQ) technique is one of the most widely used approaches because it can simultaneously analyze 8 different specimens, thus increasing throughput while reducing experimental error [17][18][19]. In this study, we used iTRAQ labeling followed by 2D-LC-MS/ MS for the quantitative proteomic analysis of the CSF and plasma samples from PNKD patients and their healthy family members to discover potential effective biomarkers for PNKD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…While their data indicated that the two MS platforms gave complementary information, they combined the data from both fractionation methods and did not provide any comparison. Larkin et al implemented HILIC in a variation of the three dimensional depletion‐free strategy initially described by Al‐Daghri, notably identifying in the order of a thousand proteins . Another alternative using anion exchange columns for fractionation is Electrostatic Repulsion‐Hydrophilic Interaction Chromatography (ERLIC), which was used by Datta et al in a study where they enriched plasma mircovesicles in a study of lacunar infarction …”
Section: Methodsmentioning
confidence: 99%
“…Larkin et al implemented HILIC in a variation of the three dimensional depletion-free strategy initially described by Al-Daghri, 39 notably identifying in the order of a thousand proteins. 57 As a non-chromatographic option, peptide isoelectric focusing has been used with both immobilized pH gradients (IPG) [59][60][61][62] and off-gel approaches. 22,34,36,63,64 Using IPG strips, Pernemalm et al have demonstrated the potential of narrow-range peptide IEF for plasma analysis.…”
Section: Fractionation Of Labeled Peptidesmentioning
confidence: 99%
See 1 more Smart Citation